THE INFLUENCE OF CONSUMER PERSONAL CHARACTERISTICS TO PERSONAL ATTITUDES ON PUCHASING COUNTERFEIT GOODS IN MANADO - Makinggung, Pricillia; Saerang, David P. E. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Shopping or buying a pirated product is a phenomenon that is common in consumer behavior and a lot going on in Indonesia. Because it is usually seen behavior of buying and selling activities of pirated products that the community will eventually assume that buying pirated products is normal and not a violation. In Manado last few years is rife with online transaction or online shopping is unfortunately much dominated by counterfeit products.This research aims to (1) analyze the influence of personal characteristics to their attitude on purchasing counterfeit goods, (2) identify which factor of personal characteristics that have the most significant influence to the attitude on purchasing counterfeit goods in Manado. This research applied multiple linear regression analysis with 100 respondents as sample of the research taken from people in Manado as consumers of counterfeit product. Occupation and economic situation, lifestyle, and personality has a significant effect to customer’s attitude and age and life-cycle stage has no significant effect to customer’s attitude. Lifestyleis the most influencing factor to the customer’s attitude on purchasing counterfeit goods in Manado. Manufacturers and marketers can work to adding counterfeit issue in the advertising program, and convince people that buying counterfeit goods is not good and will only embarass themselves.   Keywords: personal characteristics, consumer attitude